Impact of Dietary Restriction Regimens on Mitochondria, Heart, and Endothelial Function: A Brief Overview - Savencu, Cristina Elena; Linţa, Adina; Farcaş, Gianina; Bînă, Anca Mihaela; Creţu, Octavian Marius; Maliţa, Daniel Claudiu; Muntean, Danina Mirela; Sturza, Adrian (Frontiers in Physiology, 2021)
Caloric restriction (CR) and intermittent fasting (IF) are strategies aimed to promote health beneficial effects by interfering with several mechanisms responsible for cardiovascular diseases. Both dietary approaches decrease the body weight, insulin resistance, blood pressure, lipids and inflammatory status. All these favorable effects are the result of several metabolic adjustments, which have been addressed in this review, i.e., improvement of mitochondrial biogenesis, reduction of reactive oxygen species (ROS) production and improvement of cardiac and vascular function. CR and IF are able to modulate mitochondrial function via the interference with dynamics (fusion, fission), respiration and related oxidative stress. In the cardiovascular system both dietary interventions are able to improve the endothelium-dependent relaxation, reduce cardiac hypertrophy and activate antiapoptotic signaling cascades. Further clinical studies are required to assess the long-term safety in clinical setting.